PROFILING OF CANNABIS EXTRACTS AND CONSTITUENTS FOR CYTOTOXIC AND NF-KAPPA B-MODIFYING EFFECTS - Peschel, W.; Politi, M.; Appendino, G.; Constanti, A.; Heinrich, M.; Prieto, J. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Cannabis is used as co-medication by patients with cancer or inflammatory diseases. Cannabinoids are linked to the Nuclear Factor kappa B (NF-kB) which is pivotal in the cellular immune response [1]. Anti-inflammatory effects of 9- tetrahydrocannabinol (THC); cannabidiol (CBD), or cannflavin A and advantages of whole plant preparations have been reported [2,3]. Hydroethanolic traditional cannabis preparations (TCP) may thus combine effects of various co-constituents. We compared the profile of 7 cultivars by HPLC and 1H-NMR fingerprints and screened for cytotoxicity in three cancer cell lines (MTT assay) and modulation of the PMA/ TNF-alpha induced NF-kB activation (IL-6 reporter gene luciferase assay in stably transfected HeLaluc cells). We also tested pure cannabinoids and combined effects with phenolics, anti-inflammatory/cytotoxic drugs, and CB1-, CB2- and TRPV1 receptor antagonists. TCP showed cannabinoid dominance and a high portion of cannabinoid acids from unheated materials. Four markers were defined: (M1) the THC content, (M2) the total cannabinoid content, (M3) the ratio between the major cannabinoids, and (M4) the ratio between cannabinoids, cannabinoid acids and phenolics. TCP toxicity was determined by M2 and M4 but not M1 or M3 (LC50 100 µl/ml to 0.02 µl/ml). All cannabinoids proved to be equally toxic (LC50 < 5 ìM). Interestingly, this cytotoxic effect could be reverted by some phenolics. The window for non-toxic inhibition of NF-kB expression was wider for extracts than for cannabinoids. Unexpectedly, some compounds induced the activation of this nuclear factor. The interplay between polar/non-polar cannabis constituents in the activation/inhibition of NF-kB is discussed. Acknowledgements: William Ransom & Son, PLC, Hitchin (UK), European Commission (grant code COOP-CT-2004-512696) for funding, G Grassi, Roviegio (IT), TNO, Zeist (NL) for material provision References: [1] Juttler E et al. (2004) Neuropharmacol 47: 580-592, [2] Barrett ML et al. (1985) Biochem Pharmacol. 34, 2019-2024, [3] Russo E, Guy GW. (2006) Medical Hypotheses 66:234-246